Role of orthoptist in 3-year-old or school health check program for isolated region - Takeshita, Tetsuji; Yoshioka, Hisashi (JAPANESE ORTHOPTIC JOURNAL, 2007)
Purpose: Our goal is to determine the obligatory roles of orthoptists in 3-year-old or school health checks for isolated regions, where regular ophthalmologists visits are not available. Subjects and Methods: We examined 255 3-year-old children and 210 students (grade 1st-9th) in health-check programs. The visual acuity, eye position and stereo test were examined for 3-year-old children by orthoptists, and extra ocular change and eye position were examined for elementary and junior high school students by ophthalmologists. If any abnormality of eye position was detected, the orthoptist measured the quantity of deviation at near sight. Results: We found that 0.7% (2/251) of the 3-year-old subjects had abnormalities. Unfortunately, we were not able to follow the treatment to determine whether they were consulted to ophthalmologists after the initial health-check program. Among the student group, eighty four (40%) students were referred to ophthalmologists. We found, however that the referral rates varied significantly among schools. Conclusion: We conclude that more orthoptists should take part in the 3-year-old and school health check program. We recognized that a follow-up system is necessary to ensure secondary examinations by ophthalmologists. Due to limited ophthalmologist resources, we suggest that orthoptists perform eye position tests in isolated schools if necessary. Moreover, we should enlighten nurses, teachers and parents on the eye-diseases living in isolated regions.